2011
DOI: 10.1016/j.jairtraman.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An application of the airport service quality model in South Africa

Abstract: a b s t r a c tPassengers' expectations of service quality at airports are becoming increasingly important as air traffic grows. This research investigated passengers' perceptions of airport service quality at O.R. Tambo International Airport, South Africa. An existing model placing the concept of passenger expectations central to measuring an airport's specific level of performance was applied. The results proved significant in terms of the investment made by the airport in staff training and highlighted area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 1 publication
2
39
1
Order By: Relevance
“…This study which relies on the perspectives of passengers at Nigerian airports and the findings further lend weight to the claim by Lubbe, Douglas & Zambellis (2011) which states that the main measure of assessment of airport operations is the opinion of passengers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This study which relies on the perspectives of passengers at Nigerian airports and the findings further lend weight to the claim by Lubbe, Douglas & Zambellis (2011) which states that the main measure of assessment of airport operations is the opinion of passengers.…”
Section: Discussionsupporting
confidence: 53%
“…However, the focus of this study is to measure the relationship between service quality and customer satisfaction based on the expectation and perception of passengers with regards to the quality of services and points-of-service experiences in Nigerian airports. Lubbe, Douglas & Zambellis (2011) claim that the main measure of assessment of airport operations is the opinion of passengers, hence it is highly important to analyze passengers' expectations and perception in respect of Airport services. It is they who must define and evaluate services.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in the literature a variety of studies that propose level of service evaluation based on an additive method (Barros, Somasundaraswaran & Wirasinghe, 2007;Correia, Wirasingue & Barros, 2008;Han, Ham, Yang & Baek, 2012;Lubbe, Douglas & Zambellis, 2011). The additive method assumes that the overall level of a service is composed of the sum of the level of service performance of all variables, taking into consideration their relative importance (weight).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Additionally, Lubbe et al (2011) evaluated the relative importance of the service quality dimensions at an airport in South Africa using the final model of perceived service quality proposed by Fodness and Murray (2007). As an outcome, the research conducted by Lubbe et al (2011) found that the most important dimensions for passengers are the interaction dimension, the function dimension and the diversion dimension, respectively.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Using the dominance-based rough set approach, Liou, Tang, and Yeh (2011) examined different factors which impact quality of service as perceived by the customer. Lubbe, Douglas, and Zambellis (2011) emphasized that customer feedback on airport service quality varies by the type of customer.…”
Section: Literature Reviewmentioning
confidence: 99%